THE APPLICATION OF ANALYTICAL HIERARCHY PROCESS (AHP) TO DETERMINE BEST CITY FOR TEA FACTORY OPENING - Derrick, Neilson; Siallagan, Manahan Parlindungan Saragih (LPPM STIE Muhammadiah Bandung, 2023)
PT Surya Sentosa Sejahtera (PT SSS), a leading tea manufacturer in Indonesia, faces a pressing urgency to reach consumers nationwide in a cost-effective manner within the booming tea industry. The current distribution channel, originating from their facility located in Medan, North Sumatera, incurs substantial delivery costs for destinations outside Sumatra. These high logistic expenses, about fifty percent more than ideal, negatively impact the company’s profit margins and hinder expansion. In response, the company intends to construct a new facility in a more strategic location in 2025, but the optimal factory location remains uncertain. With the core objective of enhancing logistic efficiency, the study centers on utilizing the Analytical Hierarchy Process (AHP) as one of the Multi-Criteria Decision Making (MCDM) method to identify the most suitable location for establishing tea plant. The AHP method is developed through a literature review and brainstorming with five key employees who are involved in the project. Four-critical criteria are identified, consisting a total of twelve sub-criteria, leading to five alternative locations. In the criteria level, the AHP analysis indicates that Organizational Capability carries the highest weight, followed by Location, Operational Requirement and Financial Viability. At the sub-criteria level, Partnership Readiness emerges as the most significant, followed by Manufacturing Supervisor Availability, Prospective Area and Easiness to Build Distribution Network. At the alternative level, Surabaya is the most preferred site, followed by Bogor, Lampung, Batam and Makassar.